2012
DOI: 10.1371/journal.pone.0033743
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyopathy and Response to Enzyme Replacement Therapy in a Male Mouse Model for Fabry Disease

Abstract: Fabry disease is an X-linked disorder of glycosphingolipid metabolism that results in progressive accumulation of neutral glycosphingolipids, (predominately globotriaosylceramide; GL-3) in lysosomes, as well as other cellular compartments and the extracellular space. Our aim was to characterize the cardiac phenotype of male knock-out mice that are deficient in alpha-galactosidase A activity, as a model for Fabry disease and test the efficacy of Enzyme Replacement Therapy with agalsidase-beta. Male mice (3–4 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…However, in contrast to Fabry patients, an effect on the function of heart, kidney, and brain is completely absent or only very mild, and the life span is normal in αGalA-deficient mice. In particular, no ophthalmologic manifestations (Ohshima et al 1999 ) and no hearing loss (Noben-Trauth et al 2007 ) could be demonstrated, although some studies have reported slight sensorimotor alterations (Rodrigues et al 2009 ; Marshall et al 2010 ) and a marginal myocardial affection (Yoshimitsu et al 2006 ; Rozenfeld et al 2011 ; Nguyen Dinh Cat et al 2012 ). The latter could not be verified in our colony, possibly due to the extensive backcrossing towards the reference C57BL/6 strain and a strict breeding of all strains under identical conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to Fabry patients, an effect on the function of heart, kidney, and brain is completely absent or only very mild, and the life span is normal in αGalA-deficient mice. In particular, no ophthalmologic manifestations (Ohshima et al 1999 ) and no hearing loss (Noben-Trauth et al 2007 ) could be demonstrated, although some studies have reported slight sensorimotor alterations (Rodrigues et al 2009 ; Marshall et al 2010 ) and a marginal myocardial affection (Yoshimitsu et al 2006 ; Rozenfeld et al 2011 ; Nguyen Dinh Cat et al 2012 ). The latter could not be verified in our colony, possibly due to the extensive backcrossing towards the reference C57BL/6 strain and a strict breeding of all strains under identical conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas these mice accumulate a-galactosyl GSLs in tissues and develop microscopic lesions characteristic of Fabry disease, they live a normal lifespan and do not display altered blood and urine findings suggestive of organ dysfunction (7). Although subtle differences in cardiovascular function have been reported (8), the lack of litterand strain-matched control mice makes interpretation of these studies difficult. In an attempt to elicit a more robust phenotype, 1 group overexpressed Gb3 synthase in Gla KO mice (9).…”
mentioning
confidence: 99%
“…In thrombotic thrombocytopenic purpura, thrombus formation is facilitated and red blood cells are mechanically destroyed. In these diseases or animal models PAI-1 is shown to be increased (29,(33)(34)(35), suggesting that excessive S1P can increase PAI-1 and shift the fibrinolytic balance toward thrombosis.…”
Section: F E D C B Amentioning
confidence: 99%